2021
DOI: 10.1016/j.heliyon.2021.e06350
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral and immunomodulatory activity of curcumin: A case for prophylactic therapy for COVID-19

Abstract: Coronavirus disease-19 (COVID-19), a devastating respiratory illness caused by SARS-associated coronavirus-2 (SARS-CoV-2), has already affected over 64 million people and caused 1.48 million deaths, just 12 months from the first diagnosis. COVID-19 patients develop serious complications, including severe pneumonia, acute respiratory distress syndrome (ARDS), and or multiorgan failure due to exaggerated host immune response following infection. Currently, drugs that were effective against SARS-CoV are being rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
123
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(128 citation statements)
references
References 134 publications
0
123
0
5
Order By: Relevance
“…Due to the uncountable mechanisms of action addressed in this and other reviews, it has been reinforced that curcumin could serve as an adjuvant drug in COVID-19 treatment (Babaei et al, 2020;Manoharan et al, 2020;Roy et al, 2020;Soni et al, 2020;Zahedipour et al, 2020;Saeedi-Boroujeni et al, 2021;Thimmulappa et al, 2021). The multiplicity of pathophysiological responses induced by SARS-CoV-2 highlights the need for a combination of different drugs as a treatment strategy (i.e., there is no single "magic pill" for the cure of COVID-19).…”
Section: Discussionmentioning
confidence: 95%
“…Due to the uncountable mechanisms of action addressed in this and other reviews, it has been reinforced that curcumin could serve as an adjuvant drug in COVID-19 treatment (Babaei et al, 2020;Manoharan et al, 2020;Roy et al, 2020;Soni et al, 2020;Zahedipour et al, 2020;Saeedi-Boroujeni et al, 2021;Thimmulappa et al, 2021). The multiplicity of pathophysiological responses induced by SARS-CoV-2 highlights the need for a combination of different drugs as a treatment strategy (i.e., there is no single "magic pill" for the cure of COVID-19).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, curcumin reduced the penetration of immune cells and the expression of adhesion molecules and proinflammatory mediators in vascular cells [ 169 , 173 ]. The abilities of curcumin to reduce cytokine release syndrome, oxidative stress, apoptosis, and tissue damage following viral infection suggest that it can be used as a promising agent for COVID-19 treatment [ 174 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Inhibition of inflammatory cytokines by CUR is achieved through several mechanisms. CUR was reported to regulate activation of transcription factors such as activating protein-1 (AP-1) and NF-κB in stimulated monocytes and alveolar macrophages, thereby blocking expression of cytokine gene expression [56] Several studies have reported the effect of CUR in disease and recently, some studies have suggested that CUR may be useful for treating COVID-19 [57,58] due to immunomodulatory activity which reduces early inflammatory responses effectively improving the survival of severely ill hospitalised COVID-19 patients. Cytokines, particularly IL1β and IL6 are markedly elevated in severely ill COVID-19 patients and CUR may conceivably reduce the level of these cytokines [59,60].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Several studies have reported the effect of CUR in disease and recently, some studies have suggested that CUR may be useful for treating COVID-19 [ 57 , 58 ] due to immunomodulatory activity which reduces early inflammatory responses effectively improving the survival of severely ill hospitalised COVID-19 patients. Cytokines, particularly IL1β and IL6 are markedly elevated in severely ill COVID-19 patients and CUR may conceivably reduce the level of these cytokines [ 59 , 60 ].…”
Section: Origin Extraction and Therapeutic Properties Of Curcuminmentioning
confidence: 99%
See 1 more Smart Citation